2019
DOI: 10.31524/bkkmedj.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Ablation in Managing Lung Cancer: A Case Report Article Sidebar

Abstract: Lung cancer recurrence and metastasis from other organs is now frequently observed. 1 For early stages, surgery remains the first choice of treatment but recent studies reported that 2-5% of non-small cell lung cancer (NSCLC) patients later develop metastasis or tumor recurrence. 2,3 Late stage patients are not the best candidates for curative surgery due to extent of the disease, comorbidities and poor cardio-respiratory function.PIMT is a rare benign tumor that constitutes 0.7% of all lung lesions. [4][5][6]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, the clinical application of MWA for the treatment of IMT has been rarely reported due to the rarity of IMT. Saenghirunvattana et al ( 17 ) reported the case of a young patient (29 years old) with pulmonary IMT who achieved partial remission after receiving multiple treatments, including (but not limited to) three rounds of percutaneous MWA. Furthermore, no significant complications were observed during the perioperative period, which indicated that MWA monotherapy is probably applicable for the treatment of elderly patients with pulmonary IMT.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical application of MWA for the treatment of IMT has been rarely reported due to the rarity of IMT. Saenghirunvattana et al ( 17 ) reported the case of a young patient (29 years old) with pulmonary IMT who achieved partial remission after receiving multiple treatments, including (but not limited to) three rounds of percutaneous MWA. Furthermore, no significant complications were observed during the perioperative period, which indicated that MWA monotherapy is probably applicable for the treatment of elderly patients with pulmonary IMT.…”
Section: Introductionmentioning
confidence: 99%